THE INFLUENCE OF ARTIFICIAL INTELLIGENCE-GENERATED ADVERTISING ON CONSUMER PURCHASING BEHAVIOR AND INTENTIONS - Mandakh, Altan-Od; Mashlai, Tsolmon (Journal of Business and Innovation (Бизнес & Инноваци), 2025)
This study aims to identify how AI-generated content and advertising differ from traditional advertising in terms of how information influences consumer purchase behavior and intentions. The study used quantitative analysis to determine how AI-generated advertising influences consumer purchase behavior. The study found that AI-generated advertising influences consumer behavior and purchasing intention.